PENGEMBANGAN E-LKPD BERBASIS PROJECT BASED LEARNING UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK - Annifah, Annifah; Emiliannur, Emiliannur; Winarno, Nanang (Universitas Negeri Malang, 2024)
The independent curriculum supports learning that can facilitate students' critical thinking skills and utilize technology in the process. Therefore, this research aims to produce PjBL-based E-LKPD to facilitate students' valid and practical critical thinking skills. With this E-LKPD, students can improve their critical thinking abilities and skills in utilizing technology and information media. This research uses the 4D model according to Thiagarajan. However, it is limited to the development stage, namely the validity and practicality stage. Validation was conducted by 5 experts, namely 5 UNP physics lecturers and practicality was performed by teachers and students of SMAN 1 Banuhampu. The data collection instruments used were validity and practicality sheets. Technical data analysis for product validity using Aiken’s V. The object of the research is PjBL-based E-LKPD to facilitate students' critical thinking skills. The research results showed that the validity of the E-LKPD was 0.87 on the valid and practical criteria with an average score of 98% on the practical criteria. So, the research conclusion is that E-LKPD is suitable for use in the physics learning process